Perfectionism, Depression, Anxiety, and Academic Performance in Premedical Students - Sevlever, Melina; Rice, Kenneth G. (Revue canadienne de l'éducation médicale, 2010)
<!-- [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]--> This study examined differences in perfectionism, depression, anxiety, and academic performance between premedical (N = 104) and non-premedical (N = 76) undergraduate students. Results indicated that premedical students did not differ significantly from non-premedical students in perfectionistic self-criticism, personal standards perfectionism, depression, or anxiety. Perfectionistic high standards were not correlated with depression or anxiety for either group. Self-critical perfectionism was positively correlated with depression and anxiety, with comparable effect sizes, for both groups of students. Premedical students and non-premedical students drastically differed in their reported academic performance (GPA). For premedical students, PS perfectionism was related to higher GPA, however PS perfectionism in non-premedical students had a negligible effect in increasing GPA. The implications of these results for interventions and future research are discussed.